Impact of the Covid‐19 pandemic on neuropsychiatric symptoms and antipsychotic prescribing for people with dementia in nursing home settings. (27th January 2023) - McDermid, Joanne; Ballard, Clive; Khan, Zunera; Aarsland, Dag; Fox, Chris; Fossey, Jane; Clare, Linda; Moniz‐Cook, Esme; Soto‐Martin, Maria; Sweetnam, Adrienne; Mills, Kathryn; Cummings, Jeffrey; et al.
Abstract: Objectives: This study aimed to determine the impact of the Covid‐19 pandemic on neuropsychiatric symptoms and antipsychotic use in people with dementia living in nursing homes. Methods: This was a comparative analysis of baseline data from two large nursing home studies, one conducted during (COVID‐iWHELD study) and one prior (WHELD study) to the pandemic. It involves data from 69 and 149 nursing homes, and 1006 and 666 participants respectively. Participants were people with established dementia (score >1 on Clinical Dementia Rating Scale). Resident data included demographics, antipsychotic prescriptions and neuropsychiatric symptoms using the Neuropsychiatric Inventory Nursing Home version. Nursing home data collected were nursing home size and staffing information. Results: Overall prevalence of neuropsychiatric symptoms was unchanged from pre‐pandemic prevalence. Mean antipsychotic use across the sample was 32.0%, increased from 18% pre‐pandemic (Fisher's exact test p  < 0.0001). At a nursing home level, the medians for the low, medium and high tertiles for antipsychotic use were 7%, 20% and 59% respectively, showing a disproportionate rise in tertile three. Residents in these homes also showed a small but significant increase in agitation. Conclusion: There has been a significant increase in antipsychotic prescribing in nursing homes since the COVID‐19 pandemic, with a disproportionate rise in one third of homes, where median prescription rates for antipsychotics were almost 60%. Strategies are urgently needed to identify these nursing homes and introduce pro‐active support to bring antipsychotic prescription rates back to pre‐pandemic levels. Key points: The Covid‐19 pandemic has presented major challenges to the care home sector, raising the risk of worsening neuropsychiatric symptoms and antipsychotic prescribing practice Comparison of two care home samples indicates no overall change in neuropsychiatric symptoms but an 18% increase in antipsychotic prescribing The increase in antipsychotic use occurred disproportionately in one third of the 149 homes included in this study Most nursing homes have weathered the Covid‐19 pandemic and have not seen increases in use of harmful antipsychotic drugs in residents with dementia but some homes do need help to get back on track